Non-Invasive Treatment To Reduce Low Back Pain Among Treatment Acupunture, Massage, Spinal Manipulation, Yoga, And Tai Chi A Systematic Review - Cecep Eli Kosasih; Tetti Solehati; Agus Cakrahayat (Journal of Maternity Care and Reproductive Health, 2018)
Background: Low back pain (LBP) is one of the many spinal cord-positioning conditions commonly experienced by adults. Age factors affect the seriousness of trauma to the spine as in patients with osteoporosis under unusual conditions caused by radiculopathy or spinal stenosis, fracture, tumor or infection. This article aimed to identify the most effective non-invasive treatment in treating pain in Low Back Pain (LBP). Methods: cirtical review was used in making this article. Articles were collected through Medline, Google Scholar, Science Direct, Pubmed databases using the keywords: treatment, non-invasive, Low Back Pain from the quantitative studies. The selected articles were those that met the criteria based on PICO, published in the 2010-2017, and used English language. Articles were then evaluated using critical appraisal and PRISMA guides. Based on the evaluation, there are 6 (six) articles that match the purpose and criteria of review. From the literature search results found ways to reduce pain through non-invasive treatment such as Acupunture, Massage, Spinal Manipulation and Yoga can reduce LBP pain. Conclusion: The result of the literature that the most effective method of reducing pain is spinal manipulation where the effect of reducing pain can be maintained for a long time and is more applicable because without the use of aids, nevertheless treatment combined with other treatments and done on an ongoing basis will better results.Keywords: treatment, non infasif, Low Back Pain